Effects of store loyalty on shopping mall loyalty - Rabbanee, Fazlul; Ramaseshan, Balasubramanian; Wu, Chen; Vinden, Amy (Elsevier, 2012)
The key purpose of this paper is to bridge a research gap in shopping mall literature by investigating the relationship between store loyalty and shopping mall loyalty. The paper also examines the effects of perceived store value and store relationship commitment on store loyalty en-route to loyalty towards the shopping mall hosting the stores. The study shows that store loyalty influences shopping mall loyalty under certain conditions and that such an influence is moderated by the geographic distance between the consumer and the shopping mall. Further, the study found that distance has a moderating effect on the relationship between perceived store value and store loyalty, but not on the association between relationship commitment and store loyalty. The insights provided by this study offer academics, retailers and shopping mall managers a richer understanding of the relationships between store loyalty and its antecedents, customers’ distance from the mall, and shopping mall loyalty.